2002
DOI: 10.1097/00005650-200208001-00007
|View full text |Cite
|
Sign up to set email alerts
|

Studying Radiation Therapy Using SEER-Medicare-Linked Data

Abstract: There is a high level of agreement between SEER and Medicare reporting of radiation treatments after a cancer diagnosis, suggesting that either source can be used to assess radiation-related treatment patterns. However, for the most complete ascertainment of radiation use, both SEER and Medicare sources should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
190
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(195 citation statements)
references
References 7 publications
3
190
0
2
Order By: Relevance
“…SEER adheres to strict quality assessment measures by ensuring the accuracy of sample cases by reabstracting data from the medical records annually. Based on a recent studies by Virnig et al (2002), these authors found a 98% completeness in each sample case with a 490% rate in the accuracy of reporting adjuvant therapy Maggard et al, 2003). In addition, the database also appears to be accurate for major surgical procedures .…”
Section: Discussionmentioning
confidence: 99%
“…SEER adheres to strict quality assessment measures by ensuring the accuracy of sample cases by reabstracting data from the medical records annually. Based on a recent studies by Virnig et al (2002), these authors found a 98% completeness in each sample case with a 490% rate in the accuracy of reporting adjuvant therapy Maggard et al, 2003). In addition, the database also appears to be accurate for major surgical procedures .…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy was identified in the carrier claims and outpatient files using HCPCS codes (Table E1; available online at www.redjournal.org) (24). A course of radiation therapy was defined as a cluster of claims with breaks of 30 days or more between codes assumed to be indicative of a separate course of radiation therapy.…”
Section: Radiation Therapy and Providermentioning
confidence: 99%
“…Using validated claim-based algorithms, we classified patients as treated with chemotherapy if they received treatment within 4 months of NSCLC diagnosis (27). Receipt of radiation therapy was ascertained using SEER and Medicare data (28).…”
Section: Cancer-related Factors and Treatmentmentioning
confidence: 99%